(untitled) (Economic studies journal, 2021)
Abstract This research aims to analyze changes in the age structure of the Libyan population and their impact on labor supply during the period (1973-2012). It also aims to discuss the proposed population and employment policies during the upcoming period . Descriptive analysis method was used in analyzing the development of the Libyan population, population growth rates, changes in the age distribution of the Libyan population, the effects resulting from changes in the age distribution of the Libyan population, as well as analyzing population and employment policies that should be followed. The study found a set of results, the most important of which, is that the population growth rate has witnessed a remarkable decline in recent years after it was high during the beginning of the study period .This has led to a decrease in the percentage of age groups (0-14) and an increase in the proportion of age groups (15-64) in the age structure of the Libyan population .These changes in turn resulted in the emergence of the demographic dividend stage, a change in the number of economically active individuals, a decrease in the total dependency ratio, And an increase in the outputs of the educational and training system. The study recommends the initiation of a system that could undertake the tasks of developing, implementing and following up population policies, setting up a future plan to determine the target population growth rates and the proportion of appropriate age groups. The study also recommends the establishment of clear-cut employment policies through an institutional system capable of supervising, implementing and following up employment bpolicies, and strengthening cooperation and coordination between the competent authorities in Libya and the United Nations Population Fund in the areas of programs and plans related to the population policy.